A comparison of intravaginal misoprostol with sublingual misoprostol for second trimester medical termination of pregnancy - Pandey, Ankita; Kundu, Sarmila; Deshmukh, Prasad Yeshwant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Second trimester abortions generally account for less number of patients as compared to first trimester abortions as patients generally come earlier as soon as pregnancy is recognized but now days due to advent of USG many cases of fetal anomaly are detected earlier accounting for increasing number of cases of second trimester. Methods: Present study was conducted among patients with pregnancy between 13-20 weeks of period of gestation (to be randomly assigned) after getting approval from institutional ethics committee and informed consent from the patient. Participants were randomly allocated to receive 400 µg of misoprostol either sublingually or intravaginally every six hours for a maximum of 5 doses. The blood pressure, pulse rate & temperature and side effects monitored every 3 hrs. If women in either group failed to abort after 48 hours of initiation of treatment termed as failure. In cases of failure they were given additional doses of sublingual misoprostol till abortion occurred. Primary outcome variable compared was success rate at 48 hours. Secondary outcome variables compared were bleeding patterns, completeness of abortion, induction abortion interval and any side effects. Results: It has been found that vaginal misoprostol 400 micro gm achieved a success rate to 100% in 48 hours, while the success rate was 93.33% with the sublingual route. (P = 0.4915, NS). Conclusions: Thus from our limited study population, we conclude that there is no significant difference in efficacy and complications between the two routes, although a larger cohort is required to get more dependable result.